Pengaruh Penataan Tempat Duduk Terhadap Hasil Belajar IPA Kelas IV SDN 10 Palembang - Santia, Vipi; Misdalina, Misdalina; Noviati, Noviati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the effect on science learning outcomes for the fourthgrade students of SD N 10 Palembang. The method used by the researchers in this study is anexperimental method with a Nonequivalent Control Group Design research design with apopulation of all fourth grade students at SD Negeri 10 Palembang, namely as many as 25 students. The samples taken were all fourth grade students of SD Negeri 10 Palembang as the experimental group and IV B as the control group. The testing phase of the instrument used is using a test of validity, reliability, level of difficulty, and distinguishing power. Data analysis techniques used to test the average are normality test, homogeneity test, and t-test. The results of data analysis can be obtained that the average value of the experimental class students is 70.76 and the average value of the control class students is 65.83. Data collection techniques are tests and documentation. Hypothesis testing using t-test with the results obtained tcount = 2,559 and ttable = 2,069 so that tcount ttable then Ho is rejected and Ha is accepted. This means that there is a significant effect of seating arrangement on science learning outcomes for the fourth grade students of SD N 10 Palembang.